Pembelajaran Qira'ah Dasar: Studi Kasus Pada Metode Sorogan Di Pondok Pesantren: Basic Qira`ah Learning: A Case Study on the Sorogan Method in Islamic Boarding Schools - Rusdiana Fatmawati (Chalim Journal of Teaching and Learning (CJoTL), 2021)
This study is qualitative research and using a case study approach. This study aims to make a description, picture, or painting systematically, accurately, and factually about the properties, facts, and the relationship between the phenomena under investigation. The results showed that the application of the sorogan method in the An-Nahdliyyah Islamic boarding school went well and was effective for the learning process of students, especially in learning maha>rah qira>`ah. With the application of the sorogan method, students are able to read and understand the material in detail, besides that students can also enrich their insight and knowledge through direct question and answer with the ustadz (teacher in Islamic Boarding School). For the ustadz, this method is very useful to know the ability of each student in-depth, so that the cleric can find solutions to overcome learning difficulties or problems experienced by students. Hopefully, it is able to motivate the students to always be enthusiastic in learning, especially in the study of maharah qira`ah by using this sorogan method.